Liquisolid systems as a novel approach in formulation and manufacturing of solid dosage forms: Challenges and perspectives - Aleksić, Ivana; Glišić, Teodora; Parojčić, Jelena (Archives of Pharmacy, 2022)
Liquisolid systems are a novel, promising platform for the production of solid dosage forms with a high liquid content, i.e. dispersion of the drug in a suitable, hydrophilic, non-volatile liquid vehicle or liquid drug. This technology requires conventional, but highly porous excipients (carrier and coating material in the appropriate ratio) able to absorb/adsorb liquid medication, resulting in both good flowability and acceptable compression properties. This approach has shown great potential to improve the dissolution rate and bioavailability of poorly soluble drugs, and has been recognized as a good alternative to common, more complex and expensive techniques. A variety of applications of this simple technique have been investigated recently, including the preparation of: modified release tablets, orally disintegrating tablets, solid dosage forms with liquid herbal extracts, etc. This emerging technology has numerous advantages, and the most important are: simplicity, cost-effectiveness, applicability in large scale production and environmental friendliness. However, it is accompanied by certain challenges as well, such as limited applicability in the case of highly dosed drugs. This article aims to give a comprehensive overview of recent progress regarding the potential applications of this technology, as well as to give an insight into the new liquisolid-based techniques intending to further support its commercial applicability.